The Legal Consequences Of Serial Marriage For Wives And Children Are Reviewed From The Constitutional Court Decision Number 46/PUU-VIII/2010 And The Compilation Of Islamic Law On The Civil Of Children Against Fathers In Serial Marriages - Nagib, Atikah (International Significance of Notary, 2023)
Abstract : Children are gifts from God Almighty that must be maintained and protected because in children are attached dignity, dignity, and rights as human beings. For a child born from a valid marriage has a clear legal position so that obligations and rights arise between parents and children whereas, based on Article 43 of Law No. 1 of 1974 stipulates that "Children born out of wedlock only have civil relations with their mother and her mother's family". The research method used in this study is normative legal research, which uses the statutory approach method (statute approach) and conceptual approach (conceptual approach). The legal materials used are primary, secondary and tertiary legal materials and the legal material analysis techniques used in this study are qualitative descriptive analysis.The results of the research that has been conducted state that the decision of the Constitutional Court Number 46 / PUU-VIII / 2010 strengthens between religious norms and Indonesian legal norms, so that children outside marriage are entitled to their rights recognized by the state. Basically, between the decision of the Constitutional Court No. 46/PUU-VIII/2010 with article 99 KHI and article 53 KHI, all of them aim the same, namely to protect women as mothers and children before the law.  And based on the Constitutional Court Decision Number 46 / PUU / VIII / 2010 it can be that an extramarital child has a civil relationship with his father as long as it can be proven by Science. Civil relations arising from this blood relationship include legal relations of rights and obligations between children and their fathers in the form of nasab relationships, mahram relationships, rights relationships, inheritance relationships and guardianship relationships. Keywords: legal consequences of children, serial marriage, Constitutional Court rulings